Nilai-Nilai Pendidikan Islam Pada Adat Istiadat Masyarakat Pakpak Di Pesantren - Wahyudin, Wahyudin; Ma’arif, Muhammad Anas; Rofiq, Muhammad Husnur (Program Studi Pendidikan Agama Islam, 2023)
This research aims to analyze and understand in depth the values ??contained in the customs of the Pakpak community, especially in life cycle ceremonies such as the ceremony of cutting children's hair, from the perspective of Islamic religious education. This research uses a qualitative approach with a case study type at the As-syahaadah Islamic Boarding School, Maholida Village, Pakpak Bharat Regency, North Sumatra. Data was obtained through observation, interviews and documentation with Islamic Religious Education teachers, traditional leaders and the local community. The research results show that Pakpak community customs, such as wedding ceremonies, have adapted to Islamic teachings, but there are still conflicting aspects. There are efforts to reassess and review these aspects so that they are in accordance with Islamic principles. Islamic values ??were found, such as religious advice, the concept of sakinah mawaddah warmth, and Abdullah in Pakpak customs. Cultural values ??were also found, such as mutual cooperation, righteousness, love of the country, family togetherness, and religious tolerance. This research contributes to preserving local culture that aligns with religious values.